The Geographies of Social Movements : Afro-Colombian Mobilization and the Aquatic Space - Oslender, Ulrich (Book collections on Project MUSE., 2016)
In The Geographies of Social Movements Ulrich Oslender examines the activism of black communities in the lowland rain forest of Colombia's Pacific coast to show how the mutually constituting relationships between residents and their environment informs the political process.